Influencing factors of clinical efficacy of roxadustat among hemodialysis patients - Wenhui Wu; Nan Hu; Xiurong Li; Jia Di; Hua Zhou; Hongyan Niu; Min Yang (Renal Failure)
Objective To explore independent influencing factors for clinical efficacy of roxadustat in hemodialysis patients.Methods Hemodialysis patients treated with roxadustat were enrolled. The plasma trough concentrations of roxadustat were measured using liquid chromatography–tandem mass spectrometry (LC–MS/MS). A multiple logistic regression model was established to determine the factors that affect clinical efficacy of roxadustat in patients undergoing hemodialysis.Results A total of 67 hemodialysis patients were enrolled in the study. The results showed that age, blood trough concentration of roxadustat, and baseline hemoglobin (Hb) level were independent factors of clinical efficacy of roxadustat (OR = 1.06, p = .025 for age; OR = 1.001, p = .037 for plasma concentration; and OR = 0.941, p = .003 for baseline Hb), with an AUC score of 0.859.Conclusions Age, blood trough concentration of roxadustat, and baseline Hb level were independent influencing factors of the response to roxadustat in hemodialysis patients.